(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of our study was to prospectively evaluate the success, complications and recurrence following EMR of flat colonic polyps. Study Design: prospective observational study Place and Duration of Study: This study was conducted at the Lady Reading Hospital, Peshawar, Pakistan, from January 2014 to December 2016. Methods: The following ethical committee approval. Consecutive patients meeting the inclusion criteria were enrolled, and demographic data were collected. Results: A total of 243 polyps were resected in 211 patients. 23 patients had more than one polyp. Mean age was 45±13 years.En block resection was possible in 240 patients (98.8%). Bleeding immediately after resection was seen in 6 patients (2.84%) while delayed bleeding after 24 hours after the procedure occurred in 8 patients (3.8%). Perforation occurred in one patient. The overall recurrence rate was approximately 9% (18/205) during a mean follow-up of 12 months. Conclusion: Endoscopic mucosal resection is an effective and safe outpatient procedure for sessile or flat colonic polyps.